240 RISK FACTORS ASSOCIATED WITH TERM AND PRETERM LOW BIRTH WEIGHT IN THAI NGUYEN, VIETNAM. (1st January 2006) - Bui, K.; Nguyen, L.; Phung, T. T.
Abstract : Objective: LBW (< 2, 500 g) is a significant problem in both developed and developing nations. Using data from a recently completed study, this secondary analysis was performed to identify and compare the risk factors associated with term and preterm LBW. Methods: The original LBW case group was stratified into term and preterm deliveries. The control for this study was term, normal weight births (≥ 2, 500 g), derived from the original control group. Logistical regression was used to estimate odd ratios (OR) and 95% confidence intervals (CI). Results: Risk factors associated with term LBW included advanced maternal age (OR: 3.2, 95% CI: 1.6, 6.3), unmarried status (OR: 5.0, 95% CI: 1.8, 13.7), rural residence (OR: 4.1, 95% CI: 2.1, 8.0), farming occupation (OR: 1.8, 95% CI: 1.0, 3.5), shorter stature (OR: 2.7, 95% CI: 1.5, 4.9), having an unemployed partner (OR: 4.4, 95% CI: 1.7, 11.6), lower rate of weight gain (OR: 4.2, 95% CI: 2.3, 7.6), exposure to environmental tobacco smoke (ETS) (OR: 1.9, 95% CI: 1.1, 3.4), and placenta abnormality (OR: 13.9, 95% CI: 3.1, 61.9). Risk factors associated with preterm LBW were less than 3 antenatal visits (OR: 2.9, 95% CI: 1.6, 5.3), lower (OR: 10.6, 95% CI: 4.9, 23) or higher (OR: 4.5, 95% CI: 2, 10) rate of weight gain, having an unemployed partner (OR: 2.9, 95% CI: 1.2, 7.0), history of LBW infants (OR: 2.8, 95% CI: 1.7, 8.7), history of spontaneous abortion or preterm delivery (OR: 2.6, 95% CI: 1.4, 4.7), psychosocial stress (OR: 2.7, 95% CI: 1.5, 4.8), exposure to ETS (OR: 2.2, 95% CI: 1.4, 3.6), vaginal hemorrhage (OR: 7.5, 95% CI: 3.6, 15.7), placenta abnormality (OR: 7.7, 95% CI: 1.9, 31.1), gestational hypertension (OR: 2.5, 95% CI: 1.2, 5.2), and anemia (OR: 1.6, 95% CI: 1.0, 2.5). Conclusion: A comparison of the risk factors suggests potential benefits for distinguishing between term and preterm LBW deliveries in some populations.